2021
DOI: 10.1016/j.biopsych.2021.02.463
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Subcortical Neuroanatomical Signatures of Schizotypy in 2,952 Individuals Assessed in a Worldwide ENIGMA Study

Abstract: Neuroanatomical abnormalities have been reported along a continuum from at-risk stages, including high schizotypy, to early and chronic psychosis. However, a comprehensive neuroanatomical mapping of schizotypy remains to be established. The authors conducted the first large-scale meta-analyses of cortical and subcortical morphometric patterns of schizotypy in healthy individuals, and compared these patterns with neuroanatomical abnormalities observed in major psychiatric disorders. The sample comprised 3004 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 104 publications
2
1
0
Order By: Relevance
“…The brain regions identified here as directly associated with schizotypy are largely consistent with our previous meta-analysis in 3,000 individuals, 15 though not all of the associations reported here were significant in our previous meta-analysis (e.g., insula thickness). This is likely due to differences in the methods, as the former study was a meta-analysis of effects across a larger number of cohorts that used various scales to measure schizotypy (i.e., not limited to the SPQ-B, as in the present study).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The brain regions identified here as directly associated with schizotypy are largely consistent with our previous meta-analysis in 3,000 individuals, 15 though not all of the associations reported here were significant in our previous meta-analysis (e.g., insula thickness). This is likely due to differences in the methods, as the former study was a meta-analysis of effects across a larger number of cohorts that used various scales to measure schizotypy (i.e., not limited to the SPQ-B, as in the present study).…”
Section: Discussionsupporting
confidence: 91%
“…12 A recent meta-analysis from the Enhancing NeuroImaging Genetics through Meta-Analysis (ENIGMA) Schizotypy working group has identified that higher schizotypy scores, assessed using different questionnaires, were associated with thicker right medial orbitofrontal/ventromedial prefrontal cortex. 15 In studies which used only the Schizotypal Personality Questionnaire (SPQ), 11,16 increasing schizotypy levels have been inconsistently associated with smaller thalamus 17 and larger striatum (pallidum/putamen), 18 as well as thinner pars orbitalis, rostral middle frontal and parahippocampal gyri 19 and thicker right dorsolateral prefrontal cortex and dorsal premotor cortex/frontal eye fields. 17 Exposure to childhood trauma is also associated with brain morphology variations, especially in stress-sensitive limbic regions, such as the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to our findings in the chronic schizophrenia cohort, we found that ACC activity was positively (not negatively(Hager, Kirschner et al 2015)) associated to diminished expression but not apathy severity. Together with findings of preserved frontal capacity(Siever and Davis 2004) and neuroanatomy in schizotypy(Kirschner, Hodzic-Santor et al 2021), the present results suggest that in subclinical and minimally-treated stages of the psychosis continuum, more severe negative symptoms (diminished expression) are linked to an increased compensatory recruitment of cognitive capacities, operated by the ACC. This mechanism may saturate in later more chronic stages of psychosis, even though not as strongly as to impair task performance in chronic patients(Hager, Kirschner et al 2015).…”
Section: Discussionsupporting
confidence: 77%
“…18 The positive relationship between the schizotypy and schizophrenia patterns has been proved in the first metaanalysis of neuroanatomical mapping of schizotypy. 51 Furthermore, some of the previous studies have found this relation, and argued that schizotypy may lead to schizophrenia and other spectrum disorders. 10,[52][53][54][55] As per the disconnection hypothesis, the observations of schizophrenia can be generalized to schizotypy.…”
Section: Discussionmentioning
confidence: 94%